Guiding Light Selections from the Holy Qur'an (American Journal of Islam and Society, 1986)
TranslationIn the name of Allah, most benevolent, ever-merciful.Generations before youWe destroyed when theyDid wrong: their ApostlesCame to them with Clear Signs,But they would not believe!Thus do We requiteThose who sin! Surah X:13Now such were their houses, -In utter ruin,-becauseThey practised wrong-doing.Verily in this is a SignFor people of knowledge.And We saved thoseRighteousness~ Surah XXVII:52-53We have revealed for you(O men!) a book in which Is a Message for you:Will ye not then understand?How many were the populations we utterly destoryed because Of their iniquities, setting upIn their places other peoples? Surah XXI:10-11Such were the populationswe destroyed when theyCommited iniquities; but we fixed an appointed time For their destruction.  Surah XVIII:59